El inadecuado manejo de la prueba material en la escena de los hechos, preservación y análisis de las evidencias de los hechos y delitos dificultan obtener eficacia probatoria en el juicio penal. - Riofrío Guzmán, Francisco Patricio (2015)
The proof in criminal Ecuador has slowly been evolving with the passing of the years in the country today are strong new warning changes in criminal matters inescapable situation requires changes in the procedural part. The need arises to consider evidence as important elements but especially the quality with which they have been obtained and further its preservation for the time trial. Several authors indicate in the test synthesis is anything that demonstrates the discovery of truth and prove the guilt of a person presumed to have committed a crime. As proof thus allowing the necessary means to establish responsibility for the criminal conduct of one who has committed a crime, it is important to be attentive to all that this involves. So we can deduce that really on trial the evidence presented is valid and effective throughout the process, and that the remaining non-reliability into question when not handled with integrity evidence resulting from the crime scene by those who are responsibility for them and even more when the judges in the courts are responsible for valuing them. Bear in mind that the evidence and the veracity of her in criminal proceedings should be handled in a scientific sense so that fits what the law provides, within the limits of it, and above all guarantees and individual rights a fair trial, which are established in the legal framework.